GLP-1 RAs and SGLT-2 Inhibitors for Insulin Resistance in Nonalcoholic Fatty Liver Disease: Systematic Review and Network Meta-Analysis - Yan, Hongle; Huang, Chunyi; Shen, Xuejun; Li, Jufang; Zhou, Shuyi; Li, Weiping (Frontiers in Endocrinology, 2022)
Aim: To investigate the benefits of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors in improving nonalcoholic fatty liver disease (NAFLD) patients’ insulin resistance (IR). Data Synthesis: Three electronic databases (Medline, Embase, PubMed) were searched from inception until March 2021. We selected randomized controlled trials comparing GLP-1 RAs and SGLT-2 inhibitors with control in adults with NAFLD, assessed the within-study risk of bias with the Cochrane collaborative risk assessment tool RoB. Network meta-analyses were performed using fixed and random effect models. Mean difference (MD) with corresponding 95% confidence intervals (CI) were synthesized. Results: 25 studies including 1595 patients were included in this network meta-analysis. In 28.86 weeks mean treatment duration, compared with control group, GLP-1 RAs could decrease HOMA-IR (MD [95%CI]; -1.573[-2.523 to -0.495]), visceral fat (-0.637[-0.992 to -0.284]), weight (-2.394[-4.625 to -0.164]), fasting blood sugar (-0.662[-1.377 to -0.021]), triglyceride (- 0.610[-1.056 to -0.188]); on the basic of existing studies, SGLT-2 inhibitors showed no statistically significant improvement in indicators above. Compared with SGLT-2 inhibitors, GLP-1 RAs decreased visceral fat (-0.560[-0.961 to -0.131]) and triglyceride (-0.607[-1.095 to -0.117]) significantly. Conclusions: For a limited study time, GLP-1 RAs can improve IR in NAFLD effectively, while SGLT-2 inhibitors show no apparent effect on it. Systematic Review Registration: [PROSPERO], identifier [CRD42021251704].